2009
DOI: 10.2981/09-012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Responses of GPS‐Collared Female Red Deer Cervus elaphus to Driven Hunts

Abstract: Precise knowledge of how game species react to different hunting practices is a prerequisite for sound management of intensively hunted populations. We compared behavioural and spatial behaviour of five GPS‐collared female red deer Cervus elaphus in Denmark before, during and after exposure to 21 driven hunts (2–5 times each). In 53% of all hunts, deer left their normal home ranges within 24 hours, moving on average 4 km and remaining away for an average of six days. Compared to pre‐hunt values, deer moved lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 13 publications
6
53
0
Order By: Relevance
“…It is suggested that damage increases when deer are restricted in their movements, either by snow or by human disturbance (Van de Veen 1973, Maizeret andBallon 1990). Red deer seem sensitive to disturbance (Sunde et al 2009, Sibbald et al 2011, Jarnemo and Wikenros 2014 and bark-stripping level has already been related to human activity (Petrak 1998, Ligot et al 2013. The intensity of damage thus likely depends both on the availability and the quality of day-time security cover (Borkowski and Ukalski 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that damage increases when deer are restricted in their movements, either by snow or by human disturbance (Van de Veen 1973, Maizeret andBallon 1990). Red deer seem sensitive to disturbance (Sunde et al 2009, Sibbald et al 2011, Jarnemo and Wikenros 2014 and bark-stripping level has already been related to human activity (Petrak 1998, Ligot et al 2013. The intensity of damage thus likely depends both on the availability and the quality of day-time security cover (Borkowski and Ukalski 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Forageincreasing measures may thus also be used to attract ('pull') deer to sites where their presence is acceptable. As disturbance can cause red deer to leave sites (Sunde et al 2009, Sibbald et al 2011, Jarnemo and Wikenros 2014, an additional step could be to divert ('push') deer from sites where damage is undesirable (Cromsigt et al 2013). This combination of forage-increasing measures and disturbance actions-so called 'push-pull strategies' (Cook et al 2007)-merits further study.…”
Section: Recommendations For Management and Researchmentioning
confidence: 99%
“…6F and 7F) had two distinctive winter home ranges. Hunting or hunting dogs may be the cause for deer to leave its range temporary (Sweeney et al 1971;Morgantini and Hudson 1985;Vercauteren and Hygnstrom 1998;Sunde et al 2009). Management hunting was conducted at the ridgeline of Mt.…”
Section: Seasonal Home Rangementioning
confidence: 99%
“…In Japan, natural predator of sika deer (Cervus nippon centralis), wolves (Canis lupus), no longer exist since 1905, and man became the only creature to control deer population. Among human activities, hunting activities are known to affect the behavior of deer (e.g., Kufeld et al 1988;Vercauteren and Hygnstrom 1998;Sunde et al 2009), but little is known about the effect of hunting on deer migration (Kamei et al 2010).…”
mentioning
confidence: 99%
“…Kilgo et al 1998, Benhaiem et al 2008, Sunde et al 2009, Kamei et al 2010. The response to the perceived risk has also been shown to depend on hunting methods (Keuling et al 2008b), where numerous factors play a role, e.g.…”
mentioning
confidence: 99%